Copyright literacy of library and information science professionals in Bangladesh. (March 2021) - Hossain, Zakir
Library and information science (LIS) professionals often act as default copyright mavens at their institutions and, therefore, must have an awareness of copyright law and practices. Using a quantitative national survey: 'Copyright Literacy of Bangladeshi LIS Professionals' which was part of a multinational survey entitled 'Copyright Literacy of specialists from libraries and other cultural institutions', the main objective of the Bangladesh part was to illustrate the self-perceived familiarity with, knowledge and awareness of, and opinions about copyright-related issues of LIS professionals in Bangladesh. The survey also explored the existing institutional copyright policies, the need for copyright education for new and existing professionals and suggested topics for inclusion in training activities. The results show that Bangladeshi LIS professionals have conceptual knowledge and awareness of copyright issues, but overall lack an applied approach and hands-on training. This weakness is even more pronounced among LIS professionals who work in non-academic institutions. Based on these findings, it is suggested that relevant workshops, seminars and roundtable meetings focusing on copyright be organized that will pave the way for continued knowledge development around this topic.